Analisis Penerapan Standar Akuntansi Keuangan Entitas Tanpa Akuntabilitas Publik Pada Badan Usaha Milik Desa Selat - Cahyani, Suci; Sinarwati, Ni Kadek (Universitas Pendidikan Ganesha, 2021)
PThis study aimed to find out: 1) the reasons why BUMDesa does not apply SAK ETAP, 2) Implementation of SAK ETAP on BUMDesa Selat, Buleleng Regency, 3) implementation og the implementation of SAK ETAP in financial statements. This research was conducted with a qualitative descriptive method. Sources of data used are primary data and secondary data. This research was conducted in four stages :1) data collection, 2) data reduction, 3) data display, 4) verification. The results of the study show that: 1) the reason BUMDesa Pandan Harum does not apply SAK ETAP to its financial statements is because of the incompetence of human resources, and lack of awareness of the importance of complete financial statements and in accordance with SAK ETAP, 2) application of SAK ETAP at BUMDesa Pandan Harum in the preparation of financial statements, namely the income statement, show that the BUMDesa has a profit of Rp 77.583.792,00, the balance sheet shows that the total assets are Rp 1.184.806.431,37 and the passive amount is rp 1.184.806.431,37, the statement of changes in equity shows a balance of the Rp 1.242.987.240,38, the cash flow statement shows a balance of Rp 1.247.358.002,38, 3) Implementation of the application of SAK ETAP to financial reports, namely providing a financial report format that is in accordance with the applicable SAK ETAP.Keywords: Financial Statements, SAK ETAP, BUMDesa